Benign Pairs: A Significant Entity in Aspiration Cytology Smears from Breast Lesions - Monika Rathi; Pooja Kala; Atul Gupta; Satish Kumar Budania; Harshkiran Ahuja (SAGE Publishing, 2013)
Introduction Fine needle aspiration cytology (FNAC) is a reliable diagnostic tool used to diagnose breast lesions preoperatively. However, FNAC is also associated with diagnostic pitfalls. Further studies are needed to improve its diagnostic efficacy. We noticed ovoid, bare nuclei arranged in closely touching diads (benign pairs) in a significant number of cytology smears. This prompted us to assess their diagnostic utility. Materials and Methods This was a prospective study conducted in Sarojini Naidu Medical College, Agra, India. Quantitative estimation of benign pairs per 1000 ductal cells in at least 20 high power field was attempted in cytology smears of 128 cases. Results The average number of pairs in benign and malignant lesions was calculated as 7.07 ∓ 5.96 and 0.28 ∓ 0.78, respectively. Statistical analysis showed a significant difference between the number of pairs in benign and malignant cases ( P < 0.0005). Conclusions Quantitative estimation of benign pairs is helpful in distinguishing benign from malignant cases.